Clinical Features and Surgical Outcomes of Posterior Segment Intraocular Foreign Bodies in Children in East China. (25th June 2018) - Zhang, Ting; Zhuang, Hong; Wang, Keyan; Xu, Gezhi
Abstract : Purpose . To report the long-term follow-up results of posterior segment intraocular foreign body (IOFB) removal in children and to determine the prognostic factors for visual outcome. Methods . Design: retrospective, noncomparative, interventional case series; a single tertiary care center study. Participants or samples: eleven eyes (11 patients) under 16 years of age with posterior segment IOFB injuries from May 2014 to November 2017. Main outcome measures: clinical features of injury, visual acuity, and complications. Results . The mean age was 6.8 years, and the mean follow-up was 20.2 months. The main IOFB sources were accidental penetration of the eye by materials in the playground (6 cases) or by pencil lead at school (4 cases). The mean IOFB size was 3.8 (range 1–6) mm. At the last visit, the visual acuities were 20/40 or better in 40.0% of patients and better than 20/200 in 70.0%. Poor visual outcome was correlated with intraoperative rhegmatogenous retinal detachment (P = 0.0083 ). Postoperative complications included elevated transient intraocular pressure, retinal redetachment, and secondary glaucoma. Conclusions . The clinical features of pediatric posterior segment IOFBs suggest insufficient awareness of such injuries both on the playground and at school. Visual outcomes from surgical treatment were relatively favorable in this series.